Mechanism of potassium ion intercalation staging in few layered graphene from in situ Raman spectroscopy. Issue 36 (5th September 2016) - Share, Keith; Cohn, Adam P.; Carter, Rachel E.; Pint, Cary L.
Abstract : Recently emerging potassium ion (K-ion) batteries offer a lower-cost alternative to lithium-ion batteries while enabling comparably high storage capacity. Abstract : Recently emerging potassium ion (K-ion) batteries offer a lower-cost alternative to lithium-ion batteries while enabling comparably high storage capacity. Here, we leverage the strong Raman spectroscopic response of few-layered graphene to provide the first insight into the electrochemical staging sequence for K + ions in graphitic carbons. Our analysis reveals the signature of a dilute stage I compound that precedes formation of ordered intercalation compounds transitioning from stage VI (KC72 ), stage II (KC24 ), and stage I (KC8 ) and correlates electrochemical responses to the stage formation. Overall, our study emphasizes a minimum barrier to transfer the general understanding acquired for lithium-ion battery anodes to cheaper, earth abundant K-ion battery systems ideally suited for grid-scale storage.